Pengembangan kawasan pesisir melalui pembentukan Desa Wisata Sepahat Kabupaten Bengkalis - Syamsudhuha Syamsudhuha; Arisman Adnan; Afrianto Daud; Iswadi HR; Mirza Hardian; Nurhayati Nurhayati; Yennita Roza; Ahmad Jamaan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This paper aimed to develop the tourism potential of Sepahat Village, Bandar Laksamana District, Bengkalis Regency, what has been carried out, the obstacles are faced, and guidance efforts are carried out to support the realization of a tourist village, as well as recommendations that can be undertaken in the future. This community service activity used several methods, namely FGD, consultation, mentoring, and training. Focus Group Discussion (FGD) was conducted between the companion team (community service) with a team of cross-disciplinary and cross-university experts who were concerned and experienced in developing and assisting the fostered village and tourism village. FGD was also undertaken with the village head and local community leader. Consultation was carried out between local business actors, village head and community service team. Assistance was carried out between business actors directly related or as a support to tourism activities with local groups. The exploration of new economic potential in developing tourist villages, adding to the existing potential on the coast with peat soil, identifying a number of activities to encourage the realization of tourism villages, active participation and strong support from the society and local officials, gathering of society in tourism awareness groups, and also received a number of policy proposals to strengthen tourism village institutions.